2017
DOI: 10.1002/jsfa.8567
|View full text |Cite
|
Sign up to set email alerts
|

Non‐anthocyanin polyphenolic transformation by native yeast and bacteria co‐inoculation strategy during vinification

Abstract: The results of the present study demonstrate that the phenolic compounds are not drastically affected by metabolic activities of malolactic bacteria during co-inoculation and, hence, are equally suitable for wine fermentation. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…This suggested that the initial deglycosylation led P3G to the unstable aglycon, peonidin. A higher vanillic acid concentration was previously observed in O. oeni co‐inoculated wines and positively influenced the wine aroma . One possible reason for the reported increase in vanillic acid could be the breakdown of P3G.…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations
“…This suggested that the initial deglycosylation led P3G to the unstable aglycon, peonidin. A higher vanillic acid concentration was previously observed in O. oeni co‐inoculated wines and positively influenced the wine aroma . One possible reason for the reported increase in vanillic acid could be the breakdown of P3G.…”
Section: Resultsmentioning
confidence: 58%
“…A higher vanillic acid concentration was previously observed in O. oeni co-inoculated wines and positively influenced the wine aroma. 15 One possible reason for the reported increase in vanillic acid could be the breakdown of P3G. Another minor metabolite was dihydroxyphenyl acetaldehyde in the bacterial inoculated samples.…”
Section: Metabolites Produced By Degradation Of D3gmentioning
confidence: 94%
See 2 more Smart Citations
“…The aromatic profile of wines is determined by varietal aromas (from grapes), fermentative aromas (produced by yeast and LAB during fermentations) and post-fermentative aromas (associated to the aging period). The fermentative aromas clearly influence the final quality of wines, and the strains used during winemaking are responsible for the presence or absence of some flavors and other non-volatile metabolites [41]. Ethanol, carbon dioxide and glycerol are the main fermentative products.…”
Section: Fermentation End-products and Wild Microorganismsmentioning
confidence: 99%